2023
DOI: 10.3390/ijms24065633
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Microbiome and Health: Current Evidence, Controversies, and Challenges

Abstract: Blood is conventionally thought to be sterile. However, emerging evidence on the blood microbiome has started to challenge this notion. Recent reports have revealed the presence of genetic materials of microbes or pathogens in the blood circulation, leading to the conceptualization of a blood microbiome that is vital for physical wellbeing. Dysbiosis of the blood microbial profile has been implicated in a wide range of health conditions. Our review aims to consolidate recent findings about the blood microbiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…The bloodborne microbes were quite distinct between different types of cancers and the study suggests that the microbial signature in the blood could be exploited as an easy-to-access predictor not only for the presence of cancer per se but also to distinguish between different cancer types [13]. Although this study has recently been challenged [15], and the concept of a core microbiome in the blood is currently discussed very controversially [9,16], the study by Poore et al [13] provides important evidence that microbial signatures -be it in the blood or in other body sitesmight have the potential to identify cancers. Nota bene, the association of distinct bacteria with specific tumors has been shown in additional studies, and especially a study by Nejman et al [12] used a variety of techniques to detect microbes within tumors and the authors showed convincingly that the composition of the cancer-residing microbiome is distinct in each cancer type.…”
Section: Blood-borne Bacteria Might Serve As a Marker For Specific Tu...mentioning
confidence: 88%
See 1 more Smart Citation
“…The bloodborne microbes were quite distinct between different types of cancers and the study suggests that the microbial signature in the blood could be exploited as an easy-to-access predictor not only for the presence of cancer per se but also to distinguish between different cancer types [13]. Although this study has recently been challenged [15], and the concept of a core microbiome in the blood is currently discussed very controversially [9,16], the study by Poore et al [13] provides important evidence that microbial signatures -be it in the blood or in other body sitesmight have the potential to identify cancers. Nota bene, the association of distinct bacteria with specific tumors has been shown in additional studies, and especially a study by Nejman et al [12] used a variety of techniques to detect microbes within tumors and the authors showed convincingly that the composition of the cancer-residing microbiome is distinct in each cancer type.…”
Section: Blood-borne Bacteria Might Serve As a Marker For Specific Tu...mentioning
confidence: 88%
“…The human body is typically populated by over 1,000 different microbial species that colonize a variety of body sites including the intestine, urogenital tract, the lungs, and the skin, but also organs that have long been considered to be sterile, such as the liver, the pancreas, the female breast, and even blood have recently been suggested to harbor tissuespecific microbiomes [5][6][7][8][9]. These microbesconsisting of bacteria, viruses, and protozoa speciestypically form a complex ecosystem that interacts with the host and shapes the local and systemic immune response via direct interactions and via the production of metabolites with immunemodulatory properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…This limitation is due to concerns regarding potential contamination and false-positive results of identifying microbiota in this tissue. 111 , 112 No consistent microbiome results were obtained in a large-scale study of 9,770 healthy individuals. 113 Although the blood microbiome is challenging for the prediction of ICB response, it is informative for distinguishing different cancer types and healthy donors.…”
Section: Microbiota Signaturesmentioning
confidence: 98%
“…Previously, it was accepted that bacteria are present only on the skin and mucous membranes. It is now known that through some types of tissues that have the ability to flow (phenomenon of “leaky gum” and “leaky gut”) [ 4 , 5 ] bacteria and their metabolites can enter the circulation [ 6 ], and from there – various organs and tissues and be an important component of the tissue microenvironment [ [7] , [8] , [9] , [10] ]. Some organs in mammals, for example, the mammary gland, have unique, not yet fully studied mechanisms of bacterial transport from the intestine [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%